Scene Pogleda. - Soros Center for Contemporary Arts, Belgrade (Beograd : Soros Center for Contemporary Arts, 1995)
Cekic, Jovan ; Joksimovic, Zdravko ; Kacic, Darija ; Milivojevic, Era ; Naskovski, Zoran ; Pantelic, Apsolutno Zoran ; Paripovic, Nesa ; Szombathy, Balint ; Andelkovic, Dejan ; Davic, Aleksandar ; Kocic, Nina ; Markovic, Sasa ; Radovanovic, Jelica ; Sijak, Ivan ; Talent
Scene Pogleda / The Gaze Scenes, SCCA Belgrade Annual Exhibition, Soros Center for Contemporary Arts, Beograd, 2-15. oktobar 1995
boek